2012
DOI: 10.2337/db11-1468
|View full text |Cite
|
Sign up to set email alerts
|

Candesartan Cilexetil Improves Angiotensin II Type 2 Receptor–Mediated Neurite Outgrowth via the PI3K-Akt Pathway in Fructose-Induced Insulin-Resistant Rats

Abstract: We have shown previously that stimulation of the angiotensin II type 2 receptor (AT2R) results in nerve facilitation. In this study, we determined the capacity of candesartan to correct expression patterns characteristic of neuropathy and AT2R-mediated neurite outgrowth in the fructose-induced insulin-resistant rat, which is one of the human hyperinsulinemia models. Wistar rats received a 15% (w/v) fructose solution in their drinking water for 4 weeks (fructose-drinking rats [FDRs]), with or without candesarta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…We found that the FDR developed insulin resistance and the density of CGRP-LI nerve fibers in the group of FDR was markedly decreased by approximately 20%, compared with age-matched control rats (27). In contrast, administration of the AT 1 -receptor antagonist candesartan cilexetil increased the density of CGRP-LI nerve fibers to control levels (27). In addition, FDR developed the downregulation of both AT 2 -receptor neuronal function and phosphorylated Akt expression in DRG neurons (27).…”
Section: Effect Of At 1 -Receptor Blockade On Cgrpergic Disorder In Fmentioning
confidence: 93%
See 4 more Smart Citations
“…We found that the FDR developed insulin resistance and the density of CGRP-LI nerve fibers in the group of FDR was markedly decreased by approximately 20%, compared with age-matched control rats (27). In contrast, administration of the AT 1 -receptor antagonist candesartan cilexetil increased the density of CGRP-LI nerve fibers to control levels (27). In addition, FDR developed the downregulation of both AT 2 -receptor neuronal function and phosphorylated Akt expression in DRG neurons (27).…”
Section: Effect Of At 1 -Receptor Blockade On Cgrpergic Disorder In Fmentioning
confidence: 93%
“…We examined whether the depression of CGRP nerves in FDR is related to AT 2 -receptor inactivation and whether treatment with the AT 1 -receptor antagonist candesartan cilexetil improves this depressed response. We found that the FDR developed insulin resistance and the density of CGRP-LI nerve fibers in the group of FDR was markedly decreased by approximately 20%, compared with age-matched control rats (27). In contrast, administration of the AT 1 -receptor antagonist candesartan cilexetil increased the density of CGRP-LI nerve fibers to control levels (27).…”
Section: Effect Of At 1 -Receptor Blockade On Cgrpergic Disorder In Fmentioning
confidence: 95%
See 3 more Smart Citations